Effect of plant growth regulators on root nodulation of cowpea (Vigna unguiculata L. Walp) - A. Tijjani, S. Muhammad (Journal of Phytology, 2009)
The Effects of Indole – 3 – acetic acid (IAA) and naphthalene acetic acid (NAA) on the Root Nodulation of four varieties (IT95K – 499 – 35, T93K – 452 – 1, IAR 1696 and IAR 48) of Cowpea (Vigna Unguivulata L. Walp) were examined. Three concentration of IAA (0.0, 0.25 and 0.50) were applied. In the field experiment Cowpea treated at 0.1 IAA experienced a higher rate of root nodulation IRA 1696 had the highest mean of root nodulation when compared to the other three varieties of cowpea treated at 0.25 NAA experienced high mean root nodulation for IAR 48 and IT95K – 499 – 35 while IT93K – 452 – 1 and IAR1696 showed greater mean root nodulation at 0.50 of NAA treated. Result of Analysis of variance (ANOVA) showed significant difference (P > 0.001) in most parameters. These results indicate that plant growth regulator treatments improved root nodulation in Cowpea which improved high yield.